An SEM and EDS study of the microstructure of nitrate ester plasticized polyether propellants - YONG LIU; LUOXIN WANG; XINLIN TUO; SONGNIAN LI (Journal of the Serbian Chemical Society, 2010)
To probe the microstructures of nitrate ester plasticized polyether (NEPE) composite propellants and observe the morphology of each constitute in the propellant, the microstructure and elemental constitutes of NEPE propellants were investigated using scanning electron microscopy and energy dispersive X-ray spectroscopy. The ammonium perchlorate (AP) grains had a scraggy surface and were difficult to disperse uniformly. The compatibility between the AP grains and the polymer binder was poor, especially for large grains. The size distribution range of the AP and octogen (HMX) grains in propellants varied from several to several hundreds μm for the former while for the latter from several to several tens μm. Contrasting images before and after dissolution the propellant in trichloromethane showed that the degree of crosslinking of the polymer binder was low since non-crosslinked binder on the surface areas was easily removed by the solvent, and that the plasticizer was near the HMX grains and contributed more O to the element analysis of HMX.